Oxygen ion transport in doped ceria: effect of vacancy trapping - Kilic, Mehmet Emin; Lee, Jong-Ho; Lee, Kwang-Ryeol (ROYAL SOC CHEMISTRY, 2021)
Trivalent dopants in the CeO2 lattice generate oxygen vacancies in the lattice, which is vital to oxygen diffusion. However, the dopants also have two detrimental effects on the oxygen vacancy migration: trapping the oxygen vacancies in the dopant and blocking the vacancy migration by increasing the energy barrier for the vacancy transport. We studied the diffusion of oxygen in Gd doped CeO2 with La or Y co-dopants by using molecular dynamics (MD) simulation and compared them with the vacancy trapping and blocking behavior by the dopants. The trapping was characterized by the coordination number (CN) of cations statistically analyzed on a large scale. The blocking caused by the dopants was investigated by first principles nudged elastic band analysis. We found that the oxygen diffusion measured by the mean square displacement of oxygen in doped CeO2 is enhanced when the trapping of oxygen vacancies is reduced by the co-doping. In contrast, the change in the energy barrier against oxygen migration in the co-doped lattice is not consistent with the diffusion behavior. This result evidently shows that the oxygen ion transport is governed by the trapping of oxygen vacancies.
Keywords: MOLECULAR-DYNAMICS; ELECTRICAL-CONDUCTIVITY; OXIDE; STRAIN; ENERGY; ELECTROLYTES; CEO2; ASSOCIATION; STABILITY; POINTS